The effectiveness of self-efficacy enhancement for foot care program on HbA1c and foot status in people with type 2 diabetes in Thailand: A quasi-experimental study - Terathongkum, Sangthong; Lininger, Jiraporn; Nonpanya, Uraiwan (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: Diabetic foot ulceration (DFU) is a common and serious complication in people with type 2 diabetes mellitus (T2DM), leading to morbidity, lower-extremity amputation, and reduced quality of life. Effective interventions focusing on glycemic control, foot care, and exercise are essential to prevent DFU. Objective: This study aimed to evaluate the effectiveness of the 12-week Self-Efficacy Enhancement for Foot Care Program (SEFP) on HbA1c levels and foot status, including peripheral sensory loss and skin and peripheral vascular abnormalities, in people with T2DM in Thailand. Methods: A quasi-experimental study with a two-group pretest-posttest design was conducted between October 2019 and January 2020 with 80 participants (40 per group) recruited from two public health centers in Bangkok. The experimental group received SEFP plus usual nursing care, while the control group received only usual nursing care. The SEFP included diabetes education, behavior modification, foot care, and 10-chair-pose foot exercises, with home visits, telephone follow-ups, and group discussions. Data collection included demographic questionnaires, HbA1c measurements, and foot status assessments using the Semmes-Weinstein Monofilament and clinical examination of skin and vascular abnormalities. Paired t-tests, independent t-tests, and ANCOVA were used to analyze within- and between-group differences. Results: Baseline characteristics were comparable between groups. After the intervention, the experimental group showed significant reductions in HbA1c (t = 5.24, p <0.001) and significant improvements in overall foot status (t = -8.75, p <0.001), peripheral sensory loss (t = -2.97, p = 0.005), and skin and peripheral vascular abnormalities (t = -10.32, p <0.001). ANCOVA revealed significant between-group differences in post-intervention HbA1c (F = 30.56, p <0.001) and foot status measures (overall: F = 61.61, p <0.001; peripheral sensory loss: F = 11.76, p <0.001; skin and vascular abnormalities: F = 56.79, p <0.001). Conclusion: The 12-week SEFP was associated with reductions in HbA1c and improvements in foot status in people with T2DM. This program is potentially recommended for nurses in primary healthcare settings to prevent DFU and enhance clinical outcomes. Long-term studies with objective vascular measures are warranted to confirm sustained effects. Trial Registry Number: Thai Clinical Trials Registry (TCTR20250701002)